High humidity- and contamination-resistant triboelectric nanogenerator with superhydrophobic interface. (March 2019) - Zhou, Qitao; Lee, Kyunghun; Kim, Kyeong Nam; Park, Jun Gyu; Pan, Jing; Bae, Juyeol; Baik, Jeong Min; Kim, Taesung
Abstract: Triboelectric nanogenerators (TENGs) have been widely used in the recent years to harvest and convert mechanical energy to electrical energy. With the improved performance of TENGs, their stability and robustness in harsh environments have attracted increasing attention as a next challenge. We present herein a superhydrophobic interlayer-integrated TENG that exhibits high performance against humidity and environmental contamination. We used particle lithography to prepare a superhydrophobic interlayer with a three-dimensional (3D), hierarchical, porous pattern, resulting in a high static water contact angle of 161°. This 3D, hierarchical superhydrophobic interlayer played a key role in improving the TENG output performance. In addition, the TENG not only retained up to 86% of its initial electrical output at a high relative humidity of 80%, but also recovered much faster than a TENG with a regular flat interface under the same wet conditions. Finally, we found that the TENG was very robust against external contamination, maintaining approximately 88% of the initial output after five cycles of particulate contamination and washing in water, indicating that the TENGs with a superhydrophobic, 3D, hierarchical interlayer could be used for powering Internet-of-things devices that are exposed to harsh environments, such as highly humid ones with dense particulate matters. Graphical abstract: fx1 Highlights: A 3D hierarchical patterned PDMS interlayer was fabricated by particle lithography. A superhydrophobic PDMS interlayer was integrated with single-electrode TENG. The TENG showed a high and stable performance even under a highly humid environment. The TENG had a strong resistance against contamination due to self-cleaning property. The TENG can supply sustainable and durable power for IoTs in harsh environments.